Primary immune responses are negatively impacted by persistent herpesvirus infections in older people: results from an observational study on healthy subjects and a vaccination trial on subjects aged more than 70 years old - Nicoli, Francesco; Clave, Emmanuel; Wanke, Kerstin; von Braun, Amrei; Bondet, Vincent; Alanio, Cécile; Douay, Corinne; Baque, Margaux; Lependu, Claire; Marconi, Peggy; Stiasny, Karin; Heinz, Franz X.; et al. (EBioMedicine, 2022)
Advanced age is accompanied by a decline of immune functions, which may play a role in increased vulnerability to emerging pathogens and low efficacy of primary vaccinations in elderly people. The capacity to mount immune responses against new antigens is particularly affected in this population. However, its precise determinants are not fully understood. We aimed here at establishing the influence of persistent viral infections on the naive T-cell compartment and primary immune responsiveness in older adults. We assessed immunological parameters, related to CD8+ and CD4+ T-cell responsiveness, according to the serological status for common latent herpesviruses in two independent cohorts: 1) healthy individuals aged 19y to 95y (n = 150) and 2) individuals above 70y old enrolled in a primo-vaccination clinical trial (n = 137). We demonstrate a prevalent effect of age and CMV infection on CD8+ and CD4+ naive T cells, respectively. CMV seropositivity was associated with blunted CD4+ T-cell and antibody responses to primary vaccination. These data provide insights on the changes in adaptive immunity over time and the associated decline in vaccine efficacy with ageing. This knowledge is important for the management of emerging infectious diseases in elderly populations. This work was supported by the ANR (Project ANR-14-CE14-0030-01) and by Universita ItaloFrancese/Univeriste FrancoItalienne (Galileo Project G10-718; PHC Galilee Project 39582TJ), by the Swiss National Science Foundation (grant PP0033-110737 to UK), by the Heuberg Foundation (Zurich, Switzerland), by the AETAS Foundation (Geneva, Switzerland) and by a Senior IdEx Chair of the University of Bordeaux (France). EC, VB, CA, MA, DD and AT were supported by the French Government's Investissement d'Avenir Program, Laboratoire d'Excellence “Milieu Interieur” Grant ANR-10-LABX-69-01. EC and AT are supported by the Agence Nationale de la Recherche (Project RANKLthym ANR-19- CE18-0021-02).